PERLINDUNGAN HUKUM KORBAN KEJAHATAN TRANSNASIONAL TERORGANISASI DI INDONESIA (Legal Protection for Transnational Organized Crime Victims in Indonesia) - Hably Robbaany; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Transnational organized crime has become a serious threat in the current global context, especially for the security and stability of countries around the world. Indonesia, which is located at the crossroads of maritime routes and has a diversity of cultures, has the potential to be significantly affected by transnational organized crime. Apart from causing harm to the state, this transnational organized crime also harms individuals, especially for the victims who are the targets. Therefore, one important aspect in dealing with this crime is legal protection for victims. This study aims to analyze the legal protection given to victims of transnational organized crime in Indonesia. Through a normative legal approach and policy analysis, this study identifies existing legal frameworks and analyzes their effectiveness in protecting transnational organized crime victims. This research recommends several steps to increase legal protection transnational organized crime victims in Indonesia.